Farewell, king coal!. Issue 4 (8th February 2016) - Seaton, Anthony
Abstract : Coal mining provided the power for the industrial development of the West, at great cost to the health of the workforce and, from industrial pollution, of the population. Medical appreciation of the diseases of miners was slow to develop and has been marked by controversy relating to the roles of coal and quartz and the causation of emphysema. Research by the MRC and the British coal industry resolved these issues as the industry itself declined. However, from the research has come an understanding of the influence of inhalation of different inhaled pollutants on human health that has been applied to predicting and preventing possible hazards of developing nanotechnologies.